Modalizaciones discursivas en el uso de la plataforma educativa digital Moodle en el nivel superior universitario - Gutiérrez Ramírez, Luz Alejandra (2022)
The following research aims to determine, through sampling conducted with surveys, the discursive modes used by university-level students during their teaching-learning process of virtual professional academic training, implementation by the “Universidad Nacional de Trujillo”, Moodle UNTVIRTUAL. The sample population were students of the sixth cycle of the five specialties of the Secondary Education career, a survey designed to obtain the desired results according to the objectives set in the research was applied. The systematization of the research was carried out with pre-readings, readings, the collection of bibliographic sources, the design of collection instruments, analysis, understanding and interpretation of results, following the type of descriptive research for information analysis. It was concluded that discursive modalizations are significant in university students in recognition of their virtual contexts during the development of their learning processes in the Moodle platform, in addition, they identify discursive modes of access to said platform and the language that is developed in it. They recognize significantly in terms of the acquisition of the lexical range and the language with which they develop and how this has been greatly diminished in favour of their professional formation and social and academic development.